IDENTIFIKASI DETERMINAN EARNINGS QUALITY PADA PERUSAHAAN JASA TRANSPORTASI LISTED DI BEI - Aminatul Ilmiyah; Endah Tri Wahyuningtyas (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
The purpose of this study is to analyze the factors that influence firm value. The data used is data obtained from the annual reports of construction companies for the 2014-2018 period which are listed on the IDX. The sampling method used was purposive sampling, so the sample consisted of 9 construction companies from 2014 to 2018 listed on the IDX. The data analysis technique used is multiple linear regression method, namely using classical hypothesis testing and hypothesis testing for data analysis. The data will be obtained using a calculation tool in the SPPS version 25. The results of this study indicate that institutional ownership, number of audit committees, and company growth have a positive and significant effect on firm value. Ownership management, company size and profitability have a negative and significant effect on firm value. Corporate governance regarding the size of the board of commissioners, size of the board of commissioners, capital structure, business risk and debt policy do not affect firm value.